Pengaruh Senyawa Pengimbas dan Ekspresi Gen Terhadap Cekaman Kekeringan Pada Cassava (Manihot Esculenta Crantz.) - Amini, Nur Aisyah; Nurcahyani, Endang (Program Pascasarjana Universitas Papua, 2024)
ABSTRACT: : Cassava or cassava (Manihot esculenta Crantz.) is the sixth most important crop in terms of annual production. Cassava is very important as a staple food crop in tropical and subtropical regions, Africa, Asia, and South America where drought and poor soil fertility are major constraints limiting crop productivity, due to their ability to survive and produce in adverse environments. In cassava plants experiencing drought stress will inhibit cell division which will further inhibit the development of young leaves. Breeding of cassava plants needs to be done to maintain cassava productivity, both on dry land. The most effective breeding technique for cassava plants is by using molecular techniques and also applying compounds that are tolerant to drought stress. The purpose of the review journal is to find out the types of genes and compounds that can be used by plants to be resistant to drought stress in cassava. The results of reviews from several journals show that PEG 6000 and Atonic Growth Regulatory Substances (ZPT) are compounds that are tolerant to drought stress and the genes that play an important role for drought resistance in cassava are the WIN1 gene (Wax Inducer1) and the MeRAVs gene which functions to increase efficiency use of water by modifying the diffusive properties of the leaves due to the accumulation of high levels of wax.